Viscoelastic behavior of rubbery materials - Roland, C. M. (Charles Michael), 1952- (Oxford : Oxford University Press, 2011)
The gigantic size of polymer molecules makes them viscoelastic - their behavior changes depending on how fast and for how long the material is used. This book looks at the latest discoveries in the field from a fundamental molecular perspective, in order to guide the development of better and new applications for soft materials.
Title from PDF title page (viewed Sept. 5, 2011).
Also issued in print format.
Includes bibliographical references and index.
Keywords: Elastomers; Viscoelasticity